2016
DOI: 10.1155/2016/9825623
|View full text |Cite
|
Sign up to set email alerts
|

Sulforaphane Attenuates Contrast‐Induced Nephropathy in Rats via Nrf2/HO‐1 Pathway

Abstract: Background. Oxidative stress plays an important role in the pathogenesis of contrast-induced nephropathy (CIN). The aim of this study was to investigate the antioxidant effects of sulforaphane (SFN) in a rat model of CIN and a cell model of oxidative stress in HK2 cells. Methods. Rats were randomized into four groups (n = 6 per group): control group, Ioversol group (Ioversol-induced CIN), Ioversol + SFN group (CIN rats pretreated with SFN), and SFN group (rats treated with SFN). Renal function tests, malondial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
30
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 48 publications
(33 citation statements)
references
References 38 publications
(50 reference statements)
1
30
0
1
Order By: Relevance
“…HO-1, the best known downstream effector of Nrf2, is regarded as one of the most important intracellular antioxidant mechanisms [11]. Activation of the Nrf2/HO-1 antioxidant pathway contributes to protection from a variety of human diseases [11,20,21]. The present study found that hyperlipidemia increases the protein levels of Nrf2 and HO-1 in the penile tissue, which is reflexively activated when suffering from external oxidative stress.…”
Section: Discussionsupporting
confidence: 52%
“…HO-1, the best known downstream effector of Nrf2, is regarded as one of the most important intracellular antioxidant mechanisms [11]. Activation of the Nrf2/HO-1 antioxidant pathway contributes to protection from a variety of human diseases [11,20,21]. The present study found that hyperlipidemia increases the protein levels of Nrf2 and HO-1 in the penile tissue, which is reflexively activated when suffering from external oxidative stress.…”
Section: Discussionsupporting
confidence: 52%
“…Nrf2 is an important transcription factor belonging to the E26 transformation-specific (ETS) factor family that regulates the cellular resistance to oxidants, including radiocontrast agents [26]. Previous studies have shown that Nrf2 plays a renoprotective role in CIN [25,27]. Sirt3, which is an NAD + -dependent deacetylase localized in the mitochondrial matrix, regulates a variety of cellular processes, including oxidative stress, ATP generation, and energy metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…Continuous SFN intervention for 3 months also prevented the diabetic induction of renal dysfunction, fibrosis, inflammation and oxidative damage by activating the Nrf2 and its downstream antioxidant proteins in a type 1 diabetic mouse model [17]. In addition, it was validated in a rat model that SFN-induced activation of the Nrf2 signaling pathway ameliorated unilateral ureteral obstruction-induced renal damage and alleviated renal dysfunction and pathological changes caused by contrast-induced nephropathy [18, 19]. Furthermore, animals with deficient or dysfunctional Nrf2 signaling pathway are more susceptible to various kidney diseases, including acute kidney injury, lupus-like autoimmune nephritis, hyperglycemia-induced renal injury and progressive focal glomerulosclerosis [20-23].…”
Section: Discussionmentioning
confidence: 99%